Reconfigurable Bandwidth and Tunable Dual-Band Bandpass Filter Design for Ultra-Wideband (UWB) Applications - Alqaisy M.A.; Chakrabraty C.; Ali J.; Alhawari A.R.H.; Saeidi T. (Taylor and Francis Inc., 2023)
Bandpass filters; Bandwidth; Microwave filters; Optical resonators; Reconfigurable hardware; Resonators; Ultra-wideband (UWB); Dual Band; Dual-band bandpass filter; Microstrip band-pass filter; Reconfigurable; Ring resonator; Square ring resonator; Transmission zeros; Ultrawideband applications; Microstrip filters